2017
DOI: 10.1002/ece3.3216
|View full text |Cite
|
Sign up to set email alerts
|

Influence of density‐dependent competition on foraging and migratory behavior of a subtropical colonial seabird

Abstract: Density‐dependent competition for food resources influences both foraging ecology and reproduction in a variety of animals. The relationship between colony size, local prey depletion, and reproductive output in colonial central‐place foragers has been extensively studied in seabirds; however, most studies have focused on effects of intraspecific competition during the breeding season, while little is known about whether density‐dependent resource depletion influences individual migratory behavior outside the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 57 publications
4
57
1
Order By: Relevance
“…While it is well established that recording the patterns of time-activity budgets in central-place foraging can provide information on foraging traits such as habitat use and diet (e.g. Lamb, Satgé, & Jodice, 2017; Briscoe et al, 2018), fewer studies have revealed their potential for analysing keystone ontogenetic traits (e.g. Lambin & Yoccoz, 2001; Gopukumar, 2003; Benton, St Clair, & Plaistow, 2008; Fay, Barbraud, Delord, & Weimerskirch, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is well established that recording the patterns of time-activity budgets in central-place foraging can provide information on foraging traits such as habitat use and diet (e.g. Lamb, Satgé, & Jodice, 2017; Briscoe et al, 2018), fewer studies have revealed their potential for analysing keystone ontogenetic traits (e.g. Lambin & Yoccoz, 2001; Gopukumar, 2003; Benton, St Clair, & Plaistow, 2008; Fay, Barbraud, Delord, & Weimerskirch, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, bio-logging applications are still restricted to birds (particularly seabirds, e.g. Rishworth et al, 2014; Fay et al, 2016; Lamb et al, 2017), fishes (Gurarie et al, 2016) and mammals (Lambin & Yoccoz, 2001; Gopukumar, 2003; Gurarie, Andrews, & Laidre, 2009; Briscoe et al, 2018). Very few studies were conducted on insects (but see Degen et al, 2016 for bees), despite the recent availability of adapted miniaturized devices (Kissling, Pattemore, & Hagen, 2014; Nunes-Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additional work is needed to assess prey fish availability at colony sites throughout the breeding season and at Cape Cod staging areas to determine whether this hypothesis has support. Previous work in Brown Pelicans (Pelecanus occidentalis) has shown that density-dependent resource competition at breeding colonies can influence migratory behavior postbreeding (Lamb et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This dearth of information is concerning considering that staging, migration, and wintering periods comprise the majority of the avian annual cycle, and conditions during these periods may have carryover effects that influence survival and reproduction in subsequent breeding seasons (Sorensen et al 2009, Harrison et al 2011, Salton et al 2015, Szostek and Becker 2015. Additionally, conditions during the breeding season, such as resource competition, may also influence migration strategies (Lamb et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Population density is an important driver of many ecological processes and patterns, for example dispersal (Bowler & Benton, 2005;Maag, Cozzi, Clutton-Brock, & Ozgul, 2018), competition (Lamb, Satgé, & Jodice, 2017), sexual selection (Kokko & Rankin, 2006) and territoriality. Density dependence can be both positive and negative.…”
Section: Introductionmentioning
confidence: 99%